2016
DOI: 10.1007/s11127-016-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attacks and religious cleavages

Abstract: Many experts claim that the incidence of suicide attacks is driven by religious cleavages. To test this hypothesis, we investigate whether the total number of suicide attacks per violent conflict or the annual number of suicide attacks per country is associated with simmering religious conflicts. We distinguish between two kinds of religious cleavages: cleavages at the macro level between the stake holders in violent conflicts and cleavages at the micro or battle field level between the actual perpetrators and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…A rapidly expanding literature across both economics and political science has made considerable progress in our understanding of the determinants of terrorism as well as its socio-economic consequences. For instance, with respect to the drivers of terrorist activity, researchers have pointed to the roles of regime type (Gaibulloev et al 2017), education levels (Brockhoff et al 2015), ethnic or religious divisions (Gleditsch and Polo 2016;Filote et al 2016), oil revenues (Piazza 2016), and banking crises (Gries and Meierrieks 2013). Interestingly, a review of this literature by Krieger and Meierrieks (2011) highlights that institutional factors generally appear to be more important than economic ones for explaining the emergence of (transnational) terrorism.…”
Section: Introductionmentioning
confidence: 99%
“…A rapidly expanding literature across both economics and political science has made considerable progress in our understanding of the determinants of terrorism as well as its socio-economic consequences. For instance, with respect to the drivers of terrorist activity, researchers have pointed to the roles of regime type (Gaibulloev et al 2017), education levels (Brockhoff et al 2015), ethnic or religious divisions (Gleditsch and Polo 2016;Filote et al 2016), oil revenues (Piazza 2016), and banking crises (Gries and Meierrieks 2013). Interestingly, a review of this literature by Krieger and Meierrieks (2011) highlights that institutional factors generally appear to be more important than economic ones for explaining the emergence of (transnational) terrorism.…”
Section: Introductionmentioning
confidence: 99%
“…It should be recognized that the connection between religion and suicidal terrorist acts is not always supported by science and statistics. Scientists note that from 1981 to 2010, the number of suicidal terrorist acts in 35 countries of the world was 2,233; while more than 800 of them (36 %) were committed for religious reasons [16]. It is indicated that suicidal terrorist acts are often committed in order to prevent possible exit from suicidal sects and to punish the guilty [17], or for other reasons [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Filote et al [22] stated that such attacks are related to religious conflicts. They showed that religious conflicts were the major cause of suicide attacks from 1981 to 2010.…”
Section: Literature Reviewmentioning
confidence: 99%